Correlation of amodiaquine sensitivity to chioroquine and quinine against plasmodium falciparum In Vitro - Soesanto Tjokrosonto, Soesanto Tjokrosonto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1998)
Amodiaquine, a 4-aminoquinoline derivative has been introduced since decades ago, and yet the. use remains debatable for its side effects. Chioroquine, the least side effect of antimalarials possessing similarity in pharmacokinetic properties has been less attractive due to the development of resistance worldwide. The return to amodiaquine is debatable. Comparison of the level of sensitivity of 42 isolates to amodiaquine and chloroquine using in-vitro microtesting has been carried out. Amodiaquine was shown to be more sensitive to the isolates as compared to chloroquine. The reasonably high correlation with chloroquine (r=0.62; p<0.05)Â has referred the alternative treatment of chloroquine resistant falciparum to amodiaquine despite of sideÂ effects. The study concluded that amodiaquine remains an alternative drug to chioroquine resistant falciparum malaria in vitro.Key words: falciparum malaria - amodiaquine - chioroquine - quinine - in vitro